TEACHING ACCESSIBLE TRANSLATION IN TOURISM AND ITS APPLICATION IN POSTGRADUATED STUDIES - Álvarez de Morales Mercado, Cristina (2017)
The paper we present is the result of a new method used in the classes of Accessible Translation in the Master of Professional Translation at the University of Granada. This subject belongs to the unit of Audiovisual Translation and Accessibility developed since 2014 when this Master started. Our main goal was to apply the modality of accessible translation into different tourist spaces and to innovate in the teaching of translation. The methodology was based on the application of socio-constructivist theories in Accessible Translation. Specifically, we were to teach how to prepare the audio descriptions for two architectural spaces: the façade of the Granada Cathedral and the façade of the Sagrario Church, also in Granada. The audio description of these two spaces was the ideal context (macro text) for the students to go beyond the classroom, and to experience firsthand the epistemological process of translation, being able to create their target texts. In order to complete this process, the students conducted a reception study with a sight-impaired person who evaluated the accessible materials created in class. Two tools were used in the evaluation: a survey and an interview, both of which helped to measure profile variables, as well as the contents of the audio descriptions. The usefulness of these tools was expressed through the satisfaction of the sight-impaired person with the audio description presented, which met their expectations.